High-throughput kinase profiling: a more efficient approach toward the discovery of new kinase inhibitors. - Miduturu, C; Deng, X; Kwiatkowski, N; Yang, W; Brault, L; Filippakopoulos, P; Chung, E; Yang, Q; Schwaller, J; Knapp, S; King, R; Lee, J; et al. (2011)
Selective protein kinase inhibitors have only been developed against a small number of kinase targets. Here we demonstrate that "high-throughput kinase profiling" is an efficient method for the discovery of lead compounds for established as well as unexplored kinase targets. We screened a library of 118 compounds constituting two distinct scaffolds (furan-thiazolidinediones and pyrimido-diazepines) against a panel of 353 kinases. A distinct kinase selectivity profile was observed for each scaffold. Selective inhibitors were identified with submicromolar cellular activity against PIM1, ERK5, ACK1, MPS1, PLK1-3, and Aurora A,B kinases. In addition, we identified potent inhibitors for so far unexplored kinases such as DRAK1, HIPK2, and DCAMKL1 that await further evaluation. This inhibitor-centric approach permits comprehensive assessment of a scaffold of interest and represents an efficient and general strategy for identifying new selective kinase inhibitors.